HUBUNGAN PERAN ORANG TUA DENGAN KETERAMPILAN SOSIAL ANAK USIA 5-6 TAHUN SELAMA KEGIATAN BELAJAR DARI RUMAH (BDR) - Nada Ghaitsa Salsabila; Hapidin Hapidin; Hikmah Hikmah (Al Hanin, 2022)
The study aims to determine the relationship between the role of parents with the social skills of children aged 5-6 years during learning activities from home in Urban Village of Jagakarsa, South Jakarta. The sample of this research is parents who have children aged 5-6 years in Urban Village of Jagakarsa, South Jakarta. The sampling technique in this research used the cluster simple random sampling technique. The method used in this research is the correlational method. The data analysis technique uses the product moment correlation test, based on the calculation results of the Pearson product moment correlation test, the results of the Pearson correlation r are  0.769 and  are 0.361 with a significant level = 0.05 and n is 30. From the results of data analysis shows that there is a significant positive relationship between the role of parents with the social skills of children aged 5-6 years during learning activities from home in Urban Village of Jagakarsa, South Jakarta. Keywords: The role of parents, Children’s social skills, Learning activities from home